2014
DOI: 10.1007/s40093-014-0069-8
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition and nutrient release pattern of wheat (Triticum aestivum) residues under different treatments in desert field conditions of Sudan

Abstract: Background Recycling of crop residues is essential to sustain soil fertility and crop production. Therefore, it is of crucial importance to study the decomposition of crop residues particularly in the arid tropics. The decomposition and nutrient release pattern from crop residues incorporated in the soil have rarely been investigated under semiarid climatic conditions in Sudan. Decomposition and nutrient release pattern from wheat residue were investigated in a 12 week litter bag experiment under field conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 34 publications
1
9
1
Order By: Relevance
“…In dependence on precipitation, temperature, soil type, aeration, N availability, and even on the retarding presence of cover plants [88,89], wheat residues lost 27%-49% DW within 2.5-3 months [80,90,91] in accordance with the current results. Gao et al [92] recorded losses of 36.6% and 53.7% over 4 and 12 months, respectively, in wheat straw, with the decay rate decreasing slowly to 12 months upon the enrichment of lignin [93].…”
Section: Balancing Minerals In the Crop Rotation Model Wheat-wheat (Msupporting
confidence: 90%
“…In dependence on precipitation, temperature, soil type, aeration, N availability, and even on the retarding presence of cover plants [88,89], wheat residues lost 27%-49% DW within 2.5-3 months [80,90,91] in accordance with the current results. Gao et al [92] recorded losses of 36.6% and 53.7% over 4 and 12 months, respectively, in wheat straw, with the decay rate decreasing slowly to 12 months upon the enrichment of lignin [93].…”
Section: Balancing Minerals In the Crop Rotation Model Wheat-wheat (Msupporting
confidence: 90%
“…Straw decomposition is beneficial for nutrient absorption by crops and facilitates crop growth in the long term [20]. Previous studies have shown that the application of nitrogen fertilizer in high C/N straw nutrient release and promote crop growth [21]. In this study, the straw decomposition rate after non-fertilization treatment was lower than that after fertilization treatments for all periods tested.…”
Section: Discussionmentioning
confidence: 49%
“…The increase in Ca and Mg in plots treated with organic amendments may be due to the release of organic forms of these elements in the organic residue (Ogbodo 2009). The contents of Ca and Mg in decomposing organic amendments have been reported to released (Rezig et al 2014;Mubarak et al 2008) or completely immobilized (Lupwayi and Haque 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed an increased total N content in plots treated with chicken manure, sewage sludge, and combined application of sawdust and inorganic fertilizer. Organic waste with high C/N ratio such as, sawdust, wheat, rice, barley, and maize may require addition of inorganic N for decomposition to proceed (Rezig et al 2014;Debnath and Sinha 1993). Improved decomposition rates of organic amendments due to addition of inorganic N and low C/N ratio organic amendments have been reported by several workers (Rezig et al 2014(Rezig et al , 2013Debnath and Sinha 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation